First approaches in the study of cytotoxic and mutagenic damage induced by cold aqueous extract of Baccharis articulata on normal cells - Cariddi, Laura Noelia (2010)
Species of Genus Baccharis (Asteraceae) possess various bioactivities in vitro. The aim was to determine the cytogenotoxic activity of the cold aqueous extract (CAE) of Baccharis articulata. Peripheral blood lymphocytes from healthy individuals were in vitro faced to CAE (40, 78, 156, 313, 625 and 1250 ug/mL) for 18-24 h. Toxicity was evaluated by staining of trypan blue exclusion and MTT reduction. The genotoxicity was evaluated by the Micronucleus Test. Balb/c mice were injected with CAE (1800, 900 and 450 mg/kg), saline solution and cyclophosphamide as negative and positive controls respectively. Animals were sacrificed at 6 h post-injection. Bone marrow samples were fixed and stained with May- Grünwald and Giemsa. Two thousand polychromatic erythrocytes (PCE) were counted to determine number of micronuclei (MN) and normochromatic erythrocytes (NCE)/250 PCE to calculate toxicity index (TI). CAE toxicity on human lymphocytes was dose-dependent (Cytotoxic concentration 50% = 150 ug/mL). The number of MNPCE for negative control was: 5 (+1), positive control: 372 (+23) and CAE in three doses: 26 (+8), 16 (+5) and 8 (+3). TI for negative control: 1.38 (+0.35) positive control: 3.1 (+1.06) and CAE in three doses: 0.78 (+0.05), 0.82 (+0.08) and 1.21 (+0.2). CAE treatment showed no statistical difference respect to negative control. CAE of B articulata was not cytogenotoxic.